2016
DOI: 10.1038/srep33916
|View full text |Cite
|
Sign up to set email alerts
|

HB-GAM (pleiotrophin) reverses inhibition of neural regeneration by the CNS extracellular matrix

Abstract: Chondroitin sulfate (CS) glycosaminoglycans inhibit regeneration in the adult central nervous system (CNS). We report here that HB-GAM (heparin-binding growth-associated molecule; also known as pleiotrophin), a CS-binding protein expressed at high levels in the developing CNS, reverses the role of the CS chains in neurite growth of CNS neurons in vitro from inhibition to activation. The CS-bound HB-GAM promotes neurite growth through binding to the cell surface proteoglycan glypican-2; furthermore, HB-GAM abro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 40 publications
(103 reference statements)
2
53
0
Order By: Relevance
“…Recent work demonstrated the use of two-photon nanosurgery in the mouse brain to ablate single dendrites that resulted in rapid fragmentation of the distal end and formation of a retraction bulb ( Zhao et al , 2017 ). Using a prick-injury model in the cerebral cortex, another study showed dendritic regrowth by pyramidal cells after local injection of heparin-binding growth-associated molecule, an effect that was attributed to modification of the glial scar ( Paveliev et al , 2016 ). In our optic nerve injury model, RGC dendrites never regenerated unless they were stimulated with insulin, thus providing the first evidence of successful dendritic regeneration in retinal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work demonstrated the use of two-photon nanosurgery in the mouse brain to ablate single dendrites that resulted in rapid fragmentation of the distal end and formation of a retraction bulb ( Zhao et al , 2017 ). Using a prick-injury model in the cerebral cortex, another study showed dendritic regrowth by pyramidal cells after local injection of heparin-binding growth-associated molecule, an effect that was attributed to modification of the glial scar ( Paveliev et al , 2016 ). In our optic nerve injury model, RGC dendrites never regenerated unless they were stimulated with insulin, thus providing the first evidence of successful dendritic regeneration in retinal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the peptide delivered systemically following severe thoracic contusion resulted in remarkable functional recovery of the locomotor and urinary systems, possibly mediated, in part, through serotonergic sprouting and reinnervation caudal to the site of injury (221). Recently, Paveliev et al (304) have used the CS-binding protein pleiotrophin (a heparin-binding growth-associated molecule) to facilitate neural regeneration in vitro and in vivo. In preventing CS binding to PTP, they demonstrated increased sprouting following mild cortical and spinal cord injury, although this may additionally be linked to rapid reestablishment of the blood supply following trauma.…”
Section: Manipulating Chondroitin Sulfate-glycosaminoglycan Receptmentioning
confidence: 99%
“…Midkine [ 54 ] and pleiotrophin [ 55 ] partially overcome the inhibition of neurite growth by CSPGs, and improve axon regeneration in injury models of the spinal cord. Similar to its effects on neurons, pleiotrophin improved oligodendrocyte differentiation on aggrecan-coated substrates ( Fig 3B ), while its activity was markedly lower than that of PRM at the same concentrations ( Fig 3D ).…”
Section: Discussionmentioning
confidence: 99%